Critical care in paediatrics: the role of ventilation techniques in managing acute respiratory conditions - Soni, Pankaj; Cheriathu, Jenny (International Journal of Contemporary Pediatrics, 2025)
This systematic review evaluated the effectiveness of ventilation techniques in managing paediatric acute respiratory conditions, including asthma, bronchiolitis, and pneumonia. The review included 19 studies from PubMed, Scopus, Web of Science, and the Cochrane Library, published between 2015 and 2024. Findings showed that non-invasive ventilation (NIV) methods like CPAP along with BiPAP improve oxygenation and reduce intubation rates, with CPAP effective for mild cases and BiPAP for severe distress. High-flow nasal cannula (HFNC) outperformed standard oxygen therapy (SOT), though comparisons with NIV remain inconclusive. Invasive techniques like pressure-regulated volume control (PRVC) along with pressure support ventilation (PSV) are vital for unstable patients, with PRVC preventing barotrauma and PSV easing respiratory effort. Additionally, four-dimensional computed tomography (4DCT) imaging proved valuable in optimizing ventilation strategies and improving diagnostic accuracy. In conclusion, NIV techniques like CPAP along with BiPAP are effective in improving oxygenation and reducing intubation rates in paediatric respiratory conditions, with BiPAP being more suitable for severe distress. HFNC shows promise over SOT, though further comparison with NIV is needed. Invasive ventilation methods, such as PRVC and PSV, are essential for managing unstable patients, with PRVC offering protection against barotrauma and PSV enhancing respiratory efficiency. The study underscores the importance of lung-protective strategies to minimize risks in paediatric ventilation.